Adaptation of the Climate Anxiety Scale in Indonesian version: The sample of young adults - Jaro'ah, Siti; Saffana, Kuni (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2023)
The negative emotional impact of climate change has been reported in numerous studies. However, the research on the topic in Indonesia is limited, partly due to the absence of a valid scale relating to the Indonesian context. This study aims to adapt and evaluate the psychometric properties of the Climate Anxiety Scale. The adaptation of the scale into Indonesian was made concerning the International Translating Commission. The study involved 306 young people aged 18 to 35 (M= 21.01, 80.4% female) from February to June 2023. Psychometric property analysis consisted of internal consistency, Exploratory Factor Analysis (EFA), and Confirmatory Factor Analysis (CFA). The results indicate satisfactory reliability (Cronbach’s α = .91; McDonald’s ω = .91). Although most items (apart from FI5) behaved similarly to the original 2-factor structure based on EFA, they did not achieve a reasonable fit based on CFA. Therefore, the authors carefully made modifications based on modified indices of the 2-factor structure to achieve reasonable local fit measurements. The authors recommend examining the original structure using different sample categories and approaches (e.g., criterion validity) in the Indonesian sample.